HUBUNGAN MOTIVASI BELAJAR MAHASISWA DENGAN HASIL BELAJAR MENGGUNAKAN ZOOM CLOUD MEETINGS PADA MATA KULIAH MUNPEOP 5 - Raihanah Alisha Azzahra, - (2022)
This research was conducted to find out the students' learning motivation using Zoom Cloud Meetings in Munpeop 5 course, their learning outcomes using Zoom Cloud Meetings in Munpeop 5 course, and the correlation between their learning motivation and learning outcomes using Zoom Cloud Meetings in Munpeop 5 course. This research applied a quantitative approach with correlational and ex post facto research method. A causal correlation technique was used that could be interpreted as a correlation formed by cause and effect. This research is carried out by involving 54 undergraduate third-year students of the Korean Education Study Program in Indonesia University of Education who had finished the Munpeop 5 course. While the data on students' learning motivation were obtained by using a Likert-scale questionnaire, the learning outcomes were obtained through a document analysis in the forms of their final semester scores in Munpeop 5 course. The research results showed that the students' learning motivation using Zoom Cloud Meetings in Munpeop 5 course was categorized as "good", their learning outcomes using Zoom Cloud Meetings in Munpeop 5 course were categorized as "almost special", and there is a positive, significant, and quite strong correlation between the students' learning motivation and learning outcomes using Zoom Cloud Meetings in Munpeop 5 course with a correlation coefficient index of 0.567 (higher than rtable 0.266) and a significance level of 0.000 (lower than 0.050). Therefore, it could be concluded that learning motivation is one of the internal factors that functions as a stimulus and gives an influence on the students' learning outcomes.